Strategi Penganggaran Berbasis Data : Meningkatkan Akurasi dan Efisiensi Keuangan Perusahaan - Muammar Khaddafi; Najwa Balqis Aulia; Afni Dinda Anggreani; Naya Shafira; Fita Hermaya (Akuntansi, 2024)
Effective and efficient financial management is a crucial aspect in achieving organizational goals. The processes ofplanning, recording, and accountability in budget management can be enhanced through the implementation of a sound accounting system. This article discusses the importance of efficiency in budget management, including waste reduction and proper resource allocation, and how these factors can maximize desired outcomes. Additionally, the role of media as a disseminator of accurate economic information significantly influences public understanding, economic literacy, and economic stability. By enhancing transparency and accountability in financial management, society can make better decisionsandcontribute to sustainable economic growth.